Mitral valve Replacement in a 4 yrs old Child: First Time in Bangladesh - Hoque, MR; Sunny, MSA; Rahman, MM (Cardiovascular Journal, 2014)
Congenital mitral valve incompetence is a rare and complex congenital heart disease in children. We report, a case of a 4-year-old child admitted to hospital with fever, dyspnea on exertion or feeding and repeated respiratory infection for last 3 years. The transthoracic echocardiogram revealed grossly dilated left atrium and left ventricle and severe mitral regurgitation due to cleft in anterior mitral leaflet. Per-operatively mitral valve annulus was found very much dilated; leaflet thinned out and rudimentary posterior mitral leaflet. Morphology of mitral valve was totally distorted, leaflets were diminutive and beyond repairable. Mitral valve replacement was done with 25 mm Edward Life Science porcine tissue heart valve with total preservation of subvalvular structure and the patient showed dramatic symptomatic improvement and later follow up revealed good LV function with alleviation of symptoms. This is a rare and unusual case of congenital mitral valve disease with better prognosis after surgical replacement with tissue valve. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18362 Cardiovasc. j. 2014; 6(2): 167-169